Socio-Technical Design of Algorithms: Fairness, Accountability, and Transparency - Don D.H. Shin (International Telecommunications Society (ITS), 2019)
Algorithms play increasingly critical roles these days. With the conceptualization of algorithms as a socio-technical system, this study investigates the algorithm initiatives in Korea in terms of opportunities, risks, and challenges embedded in their development. It analyzes the algorithm development and trends from a critical socio-technical lens: social, technological, cultural, and industrial phenomena that represent the strategic interaction among people, technology, and society, eliciting sensitive issues of legal, cultural, and ethical rhetoric. Despite rosy predictions and proactive drives, new risks such as privacy, transparency, and fairness emerge as critical concerns of the social ramifications of algorithms and their impact on the new information milieu. With these rising issues, the questions are raised as to how to govern algorithms and how to respond to the possible outcomes that such a policy choice may have on society and industry. The socio-political implications of algorithms are discussed using Korean cases of algorithm initiatives to identify key features as the country progresses toward an algorithm-based and AI-driven society.
Keywords: 330; Algorithms; algorithm-based society; algorithm policy; socio-technical perspective; socio-technical algorithms